(untitled) (Security Dialogues, 2025)
The Balkans have been a significant region in political history. Despite being a small, mountainous country without a coastline, Macedonia’s territory has been a significant region throughout history, attracting the attention of major powers due to its strategic location. Following the breakup of Yugoslavia in 1991, Macedonia declared its independence. During this period, Greece reacted strongly against the independence. In this context, North Macedonia has been experiencing a name and other crisis. According to Greece, Macedonia doesn’t have the territory to use this name, flag, and the national anthem. In addition, they blame to Macedonia with appropriate to Greek cultural values as, Vergina Sun, Alexander the Great. Also, the statue of Alexander the Great built in the center of Skopje, renaming of Skopje airport to “Alexander the Great Airport,” and the description of the Thessaloniki Tower on the Macedonian currency have all been perceived as provocative actions by Greece. Greece identifies Macedonia’s historical and cultural heritage with its own identity, while the presence of minorities also raises concerns. Additionally, the fact that the preamble of the “Constitution of the Republic of Macedonia” states that the principles of the 1944 ASNOM Declaration are inherited and emphasizes that Macedonians living in the territories of Greece and Bulgaria will be united under the Macedonian Socialist Republic, constitutes one of the main reasons for Greece’s concerns. Greece has clearly opposed the use of the name “Macedonia” by rejecting both the existence of the Macedonian minority living within its borders and the recognition of the Macedonian nation. Greece has created international pressure for the resolution of the name issue by blocking Macedonia’s NATO and European Union membership process. After the discussions, the Prespa Agreement was signed in 2018 (Gounaris & Kofos, 2019).